THE EFFECT OF GIFT GIVING ON STUDENTS’S LEARNING MOTIVATION IN GRADE VIII SMP AL-FALAH PONDOK MELATI IN SOCIAL STUDIES SUBJECTS - Ayu Fitri Syahri; Hafifi . (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2023)
The purpose of this study is to find out about the effect of giving gifts on the learning motivation of grade VIII students of SMP Al-Falah Pondok Melati in social studies subjects for the 2022/2023 school year. This type of research is quantitative research with an experimental type. The subjects of this study were grade VIII students with a sample of 157 from 258 populations. Data collection techniques were taken using questionnaires with a Likert scale of 1-5. The instrument used was the attitude scale of giving gifts and social studies learning motivation. Testing the hypothesis of this research is to use descriptive analysis and simple regression analysis. From this study it can be seen that there is an effect of giving gifts on the learning motivation of class VIII students of SMP Al-Falah. From the statistical hypothesis it was concluded that there was an effect of giving gifts on learning motivation of 6.8% and rounded up to 7%.